PENGGUNAAN ASAS-ASAS FILOSOFIS DALAM PENGEMBANGAN DAN PELAKSANAAN KURIKULUM MERDEKA - Cintya Permatasari Pata’dungan; Misel Pilemon; Noflianti Rapang; Mari Manggauali; Dina Dina (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research aims to analyze the use of philosophical principles in the development and implementation of the "Kurikulum Merdeka" (Independent Curriculum). The "Kurikulum Merdeka" is an educational approach that emphasizes student autonomy and flexibility in learning. In this study, we explore how philosophical principles, such as epistemology, axiology, and ontology, are utilized in formulating, developing, and executing the "Kurikulum Merdeka." The research methodology involves the analysis of education policy documents related to the "Kurikulum Merdeka," and a study of philosophical literature. The research findings indicate that philosophical principles play a significant role in the design and implementation of the "Kurikulum Merdeka." Epistemology is used to shape perspectives on how students acquire knowledge and skills, while axiology influences the values emphasized within this curriculum. Ontology, on the other hand, informs the understanding of students as unique individuals. The research findings will provide deeper insights into the philosophical foundations of the "Kurikulum Merdeka" and how these principles impact education in practice. The implications of this research can contribute to more focused curriculum development based on strong philosophical principles. Additionally, this study can serve as a foundation for further reflection and discussion within the context of student-centered and self-directed learning.